Perivascular space imaging during therapy for medulloblastoma - Ruitian Song; John O. Glass; Shengjie Wu; Yimei Li; Giles W. Robinson; Amar Gajjar; Thomas E. Merchant; Wilburn E. Reddick (PLoS ONE, 2025)
Perivascular spaces (PVS) are fluid filled compartments surrounding the small blood vessels in the brain. The impact of radiotherapy and chemotherapy on PVS remains unclear. The aim of this study is to investigate treatment effects of radiotherapy and chemotherapy at four time points (TPs) in pediatric medulloblastoma (MB) patients. We examined 778 scans from 241 MB patients at baseline (0M), after 12 weeks (about 3 months) of radiotherapy and rest (3M), after chemotherapy completion (12M), and a follow-up (FollowUp) at 18- or 21-months post-baseline. PVS was segmented by applying Frangi filter on the white matter regions on T1 weighted images acquired at 3T Siemens MRI scanner using MPRAGE. PVS volume and ratio, defined as the ratio of PVS volume to the white matter volume, were measured at the four TPs. The data was first statistically analyzed using a full model where all data were included, then a paired model, which included only patients who completed consecutive measurements under the same anesthesia and shunt conditions. Both the full model and paired model showed that PVS (including ratio and volume) increased at 3M post-radiotherapy compared to baseline. During chemotherapy, PVS decreased significantly from 3M to 12M. Subsequently, from 12M to FollowUp, PVS increased again. MRI exams under anesthesia exhibited significantly lower PVS than those without anesthesia. Patients who had undergone a shunt procedure exhibited a significantly reduced PVS compared to those who had not undergone the procedure. We concluded that craniospinal irradiation led to an elevated PVS. Conversely, chemotherapy or time post-irradiation decreased PVS. Anesthesia and shunt procedures can also influence perivascular space ratio or volume.